2020
DOI: 10.1007/s11523-020-00736-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Adverse Events Associated with Cabozantinib Treatment in Patients with Advanced Hepatocellular Carcinoma

Abstract: Cabozantinib is an oral multikinase inhibitor whose targets include vascular endothelial growth factor receptors, MET, and the TAM family of kinases (TYRO3, AXL, MER). Cabozantinib is approved for patients with advanced hepatocellular carcinoma who have been previously treated with sorafenib, based on improved overall survival and progression-free survival relative to placebo in the phase III CELESTIAL study. During CELESTIAL, the most common adverse events (AEs) experienced by patients receiving cabozantinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…During the study, the most common events were palmar-plantar erythrodysesthesia, hypertension, increased aspartate aminotransferase levels, fatigue, and diarrhea. These AEs can be successfully managed by the adopted strategy of supportive care and dose modifications [163]. The comparative cost-effectiveness studies from Germany and the United States found that cabozantinib is not cost-effective compared to that of the best supportive care [164].…”
Section: Cabozantinibmentioning
confidence: 99%
“…During the study, the most common events were palmar-plantar erythrodysesthesia, hypertension, increased aspartate aminotransferase levels, fatigue, and diarrhea. These AEs can be successfully managed by the adopted strategy of supportive care and dose modifications [163]. The comparative cost-effectiveness studies from Germany and the United States found that cabozantinib is not cost-effective compared to that of the best supportive care [164].…”
Section: Cabozantinibmentioning
confidence: 99%
“…Although observational studies have reported a median initial dose of cabozantinib at 40 mg [56], clearance of cabozantinib is variable among patients; therefore, modification to the initial dose is generally not recommended except for patients using concomitant medications with potential drug-drug interactions or those with moderate hepatic impairment. The preferred dosing strategy is to initiate cabozantinib at the 60-mg dose but to implement dose reduction promptly to address tolerability, particularly in the first few months of treatment when most adverse events emerge [57].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…[2][3][4][5][6] There are only few reported cases of cabozantinib-related osteonecrosis of the jaw. 7,8 Cabozantinib is an oral multikinase inhibitor whose targets include vascular endothelial growth factor receptors, which might be the cause for osteonecrosis. This case demonstrates an underreported side effect of cabozantinib, which might be overlooked or mistaken for osseous metastasis but has a decisive impact on further oncological management.…”
Section: Figurementioning
confidence: 99%
“…Medication-related osteonecrosis of the jaw is a well-described complication of antiresorptive and antiangiogenic medications, predominantly seen in patients receiving bisphosphonate treatment, because of their combined effects on bone remodeling and angiogenesis 2–6 . There are only few reported cases of cabozantinib-related osteonecrosis of the jaw 7,8 . Cabozantinib is an oral multikinase inhibitor whose targets include vascular endothelial growth factor receptors, which might be the cause for osteonecrosis.…”
mentioning
confidence: 99%